Argentinian combed cashmere dehairing trial - Sacchero, Diego Mariano; Maurino, Maria Julia (Edición del Autor, 2018)
In an area of 30,000 km2 in the north of the Neuquén province (Argentine), about 1,500 small stockholders maintain around 390,000 goats (SENASA 2014). In this livestock production system, the Criolla Neuquina breed (CCN) is the main resource for the rural population, with meat as a main product and fiber appearing as potential complement of incomes. Morphologically, the CCN has two ecotypes, differentiated by the fleece type. Animals with short hair ("pelado") and long hair ("chilludo") are found. Fleeces of both ecotypes have a double layer of fibers, fine and soft downy fibers (cashmere or down) mixed with coarse guard hairs (hair). In the fleece there are also different proportions of vegetables, dust, peeling cells and secretions of the skin. The main attributes that define the quality of the cashmere are diameter and length of the fibers, colour and proportion of down to hair in relation to the total weight of the fleece (yield). In different research from northern Neuquén goats, cashmere diameter of 19.0 microns and length of 39.0 mm has been reported. The predominant colours of these fibers are white, beige and grey.